2023
DOI: 10.3390/nu15061402
|View full text |Cite
|
Sign up to set email alerts
|

Early Probiotic Supplementation of Healthy Term Infants with Bifidobacterium longum subsp. infantis M-63 Is Safe and Leads to the Development of Bifidobacterium-Predominant Gut Microbiota: A Double-Blind, Placebo-Controlled Trial

Abstract: Bifidobacteria are important intestinal bacteria that provide a variety of health benefits in infants. We investigated the efficacy and safety of Bifidobacterium longum subsp. infantis (B. infantis) M-63 in healthy infants in a double-blind, randomized, placebo-controlled trial. Healthy term infants were given B. infantis M-63 (n = 56; 1 × 109 CFU/day) or placebo (n = 54) from postnatal age ≤ 7 days to 3 months. Fecal samples were collected, and fecal microbiota, stool pH, short-chain fatty acids, and immune s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 64 publications
(71 reference statements)
1
11
0
4
Order By: Relevance
“…For instance, it has been demonstrated that B. animalis HY8002 raises the IgA level in PP cells [ 21 ], and B. longum subsp. infantis M-63 can also significantly increase fecal IgA levels [ 20 ]. In this study, B. longum subsp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, it has been demonstrated that B. animalis HY8002 raises the IgA level in PP cells [ 21 ], and B. longum subsp. infantis M-63 can also significantly increase fecal IgA levels [ 20 ]. In this study, B. longum subsp.…”
Section: Discussionmentioning
confidence: 99%
“…Supplementation with B. longum subsp. infantis M-63 significantly upregulated the relative abundance of Bifidobacterium , resulting in elevated fecal IgA levels [ 20 ]. Additionally, B. animalis positively impacted IgA levels in a mouse model and improved intestinal barrier function [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The obtained paired-end FASTQ data from the registered data in the cohort study were trimmed and merged before selection of the amplicon sequence variants (ASVs). The classification and diversity analysis of the ASVs were performed using the QIIME2 software package, version 2022.8 (https://qiime2.org/ accessed on 29 December 2022), as described previously [14]. Taxonomic classification was performed using the naive Bayes classifier trained on Greengenes2, version 2022.10 (https://greengenes2.ucsd.edu/ accessed on 2 February 2023), with a 99% threshold for full-length sequence operational taxonomic units.…”
Section: Bioinformatics Analysismentioning
confidence: 99%
“…The supplementation primarily influenced the genus Bifidobacterium . These findings indicated that administering B. infantis M-63 at a dose of 1 billion per day to healthy full-term infants has a beneficial effect on maintaining infant health by promoting the development of the intestinal microbiota [ 148 ].…”
Section: Role Of Infant Gut Microbiota In the Immune Responsementioning
confidence: 99%